The Adjusted Cut-Off Value of Interferon-Γ Release Assays (IGRA) to Diagnose LTBI in Indonesia - Denada Florencia Leona (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
Latent Tuberculosis Infection (LTBI) is as a condition when Mycobacterium tuberculosis (MTB) persists in the body without causing symptoms while maintaining viability with the possibility to become active tuberculosis in the future. The detection of LTBI is an important strategy from WHO to end the chain of tuberculosis. LTBI can be diagnosed by using the IGRA test. IGRA uses specific antigens of MTB, early antigenic target-6 (ESAT-6), to induce interferon-gamma production by antigen-specific T cells. In the IGRA test, the cut-off value is explicitly needed to distinguish healthy people from LTBI patients. This study aimed to find IGRA's adjusted cut-off value in Indonesia. The subjects were 150 people, which were 50 healthy people, 50 subjects with active TB, and 50 with suspected LTBI. Isolated Lymphocytes derived from PBMC sand were cultured in a complete RPMI medium and induced by Esat-6 for six days. IFN-g levels were assayed from supernatants by the sandwich Elisa technique. Statistical analysis was used to determine cut-off values for IFN-g derived from healthy and diseased patients. The highest aptitude index (κ value) that could discriminate between healthy and LTBI groups was 0.925 at a concentration of 0.792 ng/ml of IFN-g, hence the cut-off value to diagnose LTBI was 0.792 ng/ml of IFN-g. Based on this value, out of 40 suspected cases of LTBI, up to 17 (42.5%) and 23 without LTBI (57.5%) were found. So, the conclusion was that the adjusted cut-off value for IFN-g to diagnose LTBI in Indonesia was 0.792 ng/ml.